Strength and function across maturational levels in young athletes at the time of return to sport after ACL reconstruction - Ithurburn, M. P.; Paljieg, A.; Thomas, S.; Hewett, T. E.; Paterno, M. V.; Schmitt, L. C. (Sports Health: A Multidisciplinary Approach, 2019)
Background: The impact of maturation on lower extremity strength and function after anterior cruciate ligament reconstruction (ACLR) may help guide future studies of age-specific rehabilitation.